2018
DOI: 10.1063/1.5005913
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into the magnetic dead layer in La0.7Sr0.3MnO3 thin films from temperature, magnetic field and thickness dependence of their magnetization

Abstract: Experimental investigations of the magnetic dead layer in 7.6 nm thick film of La0.7Sr0.3MnO3 (LSMO) are reported. The dc magnetization (M) measurements for a sample cooled to T = 5 K in applied field H = 0 reveal the presence of negative remanent magnetization (NRM) in the M vs. H (magnetic field) measurements as well as in the M vs. T measurements in H = 50 Oe and 100 Oe. The M vs. T data in ZFC (zero-field-cooled) and FC (field-cooled) protocols are used to determine the blocking temperature TB in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The NRM effect appears in a material when the direction of M is reverse to the direction of the applied H to that material 35 . NRM has been already observed and reported by our group in LSMO thin films grown in 100 mTorr 35,39 . Lee et al have also observed NRM in LSMO films via X-ray magnetic circular dichroism (XMCD) technique 34 .…”
Section: Magnetic Properties Of Lsmo Thin Filmssupporting
confidence: 73%
See 4 more Smart Citations
“…The NRM effect appears in a material when the direction of M is reverse to the direction of the applied H to that material 35 . NRM has been already observed and reported by our group in LSMO thin films grown in 100 mTorr 35,39 . Lee et al have also observed NRM in LSMO films via X-ray magnetic circular dichroism (XMCD) technique 34 .…”
Section: Magnetic Properties Of Lsmo Thin Filmssupporting
confidence: 73%
“…This NRM has been observed only when the measuring field is less the coercive field (H c ) since for applied H > H c only positive values of M are observed in ZFC. This observed NRM is attributed to the coexistence of magnetically inhomogeneous regions consisting of spin clusters of a lower oxidation state and the ferromagnetic order in LSMO thin films 35,39,[41][42][43] . The growth pressure dependence of NRM is plotted in Fig.…”
Section: Magnetic Properties Of Lsmo Thin Filmsmentioning
confidence: 93%
See 3 more Smart Citations